2004
DOI: 10.1002/clc.4960271207
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of acute pulmonary embolism on echocardiographic doppler indices and functional capacity

Abstract: SummaryBackground and hypothesis: Hemodynamic and functional consequences of acute pulmonary embolism (APE) are believed to be reversible with antithrombotic treatment. To verify this hypothesis, we reassessed our patients at least 1 year after an episode of APE.Methods: We compared echo Doppler indices and 6-min walking test parameters (6-MWT) of 36 patients (13 men, 23 women, age 66 ± 11 years), studied on average 3.1 ± 2.2 years after an acute episode of pharmacologically treated massive or submassive APE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Previously, it was reported that survivors of APE do present larger diameters of RV when compared to age and sex matched controls [9]. However, myocardial injury was not evaluated in this study.…”
mentioning
confidence: 87%
“…Previously, it was reported that survivors of APE do present larger diameters of RV when compared to age and sex matched controls [9]. However, myocardial injury was not evaluated in this study.…”
mentioning
confidence: 87%
“…31 RV damage sustained at the time of the PE can reduce the heart's ability to adapt to exercise. [32][33][34][35] In one study of PE patients with high pulmonary pressures on admission, 57% treated with anticoagulation alone had residual pulmonary arterial hypertension after 28 months of follow up. 21 In a separate study of 144 anticoagulated submassive PE patients, 27% of patients were found to have higher pulmonary pressures at the 6-month follow up than at the initial presentation.…”
Section: Question 3: Can Thrombolytic Therapy Improve Long-term Outcomentioning
confidence: 99%
“…In spite of the low accuracy of echo-Doppler to correctly measure the degree of PH [4,5], echocardiography remains to date the most utilized and often the only method to investigate, both in the acute phase and over time, the course of pulmonary artery systolic pressure (PAsP). Several studies considered the echocardiographic follow-up at least 6 months after an episode of acute PE [6][7][8][9][10][11][12][13][14]. Some of them [13,14] correlated the value of echocardiographycally derived PAsP in the acute phase with the persistence of PH 12 or 16 months later.…”
Section: Introductionmentioning
confidence: 99%